The impact of playing a snakes and ladders game about Mount Merapi disaster awareness on students' preparedness knowledge at Kepuharjo Cangkringan Elementary School - nugroho, ariyanto; Rahmuniati, Merita Eka; Sahayati, Sri; Polnesta Ita, Maria Denliana (Journal of Health Education, 2025)
Background: Indonesia is a country that is highly susceptible to natural disasters, particularly due to the frequent volcanic eruptions occurring on the island of Java. This situation underscores the importance of ensuring that students in disaster-prone regions are well-prepared for such events. Traditional outreach methods have often been deemed insufficient in enhancing students' understanding of disaster preparedness. In response to this challenge, this research introduces an innovative educational tool: modified "Disaster Snakes and Ladders" game. This game aims to improve students' readiness for a specific focus on the potential eruptions of Mount Merapi. The study’s objective is to evaluate the effectiveness of the game in enhancing the understanding of disaster preparedness among students at Kepuharjo State Elementary School. Method: Employing a quasi-experimental design with a one-group pre-test and post-test approach, the study selected fifty students through total sampling. Data collection involved administering questionnaires before and after game implementation. Analysis using the Wilcoxon Signed-Rank Test revealed promising results: initial scores averaged 17.08, increasing to 17.92 post-test. Statistical significance was confirmed  p-value of 0.016, indicating a substantial improvement in students' disaster preparedness knowledge. Conclusion: the Disaster Snakes and Ladders game effectively enhances elementary students' awareness and understanding of disaster preparedness, specifically geared towards Mount Merapi-related disasters.